2022
DOI: 10.1021/acsbiomedchemau.2c00040
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Silica Nanoparticle Protein Corona Compositions Exposed to Male and Female BALB/c Mice Plasmas

Abstract: As various nanoparticles (NPs) are increasingly being used in nanomedicine products for more effective and less toxic therapy and diagnosis of diseases, there is a growing need to understand their biological fate in different sexes. Herein, we report a proof-of-concept result of sex-specific protein corona compositions on the surface of silica NPs as a function of their size and porosity upon incubation with plasma proteins of female and male BALB/c mice. Our results demonstrate substantial differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 80 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…This protein corona is a primary driver of nanoparticle distribution and elimination, mediating both desired interactions (such as uptake of the nanoparticle by target cells) as well as undesired interactions (such as nanoparticle opsonization by circulating immune cells) (Tran and Roffler, 2023). Ashkarran and others concluded that protein corona composition was distinct for silica nanoparticles exposed to female versus male mouse plasma (Ashkarran et al, 2023), which may be a critical finding for the field. However, it should be noted that their results are reported from experiments involving plasma that was pooled from 3 female versus 3 male mice, yielding a single sample of plasma for each sex.…”
Section: Sex Differences In Nanomedicine Interaction With Cells and F...mentioning
confidence: 99%
“…This protein corona is a primary driver of nanoparticle distribution and elimination, mediating both desired interactions (such as uptake of the nanoparticle by target cells) as well as undesired interactions (such as nanoparticle opsonization by circulating immune cells) (Tran and Roffler, 2023). Ashkarran and others concluded that protein corona composition was distinct for silica nanoparticles exposed to female versus male mouse plasma (Ashkarran et al, 2023), which may be a critical finding for the field. However, it should be noted that their results are reported from experiments involving plasma that was pooled from 3 female versus 3 male mice, yielding a single sample of plasma for each sex.…”
Section: Sex Differences In Nanomedicine Interaction With Cells and F...mentioning
confidence: 99%
“…For instance, depending on the biological sex, LNPs may undergo different processing, encountering unique biological environments associated with each biological sex. Indeed, biological sex-dependent protein corona formation has been reported [ 27 ], suggesting that the biological sex of the host could impact the interaction between LNPs and proteins in the body. Any differences in the protein corona may change LNP surface properties, which in turn could impact cellular uptake and the processing of LNPs and, hence, affect biodistribution, clearance, and expression profiles [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This complexity arises primarily from the phenomenon of protein/biomolecular corona formation on the surface of nanoparticles. The protein corona represents a layer of biomolecules, predominantly proteins, that spontaneously adhere to the nanoparticle surface upon exposure to biological fluids. Consequently, what bacteria encounter in vivo are not the pristine nanoparticles but rather the nanoparticles coated with this protein corona. …”
mentioning
confidence: 99%